Surface Self‐Assembly Protonation Triggering Triple‐Conductive Heterostructure with Highly Enhanced Oxygen Reduction for Protonic Ceramic Fuel Cells. Issue 49 (30th October 2022) - Zhang, Xiaoyu; Song, Rui; Huan, Daoming; Zhu, Kang; Li, Xinyu; Han, Hairui; Xia, Changrong; Peng, Ranran; Lu, Yalin
Abstract: Triple‐conducting (H + /O 2− /e − ) cathodes are a vital constituent of practical protonic ceramic fuel cells. However, seeking new candidates has remained a grand challenge on account of the limited material system. Though triple conduction can be achieved by mechanically mixing powders uniformly consisting of oxygen ion–electron and proton conductors, the catalytic activity and durability are still restricted. By leveraging this fact, a highly efficient strategy to construct a triple‐conductive region through surface self‐assembly protonation based on the robust double‐perovskite PrBaCo1.92 Zr0.08 O5+δ, is proposed. In situ exsolution of BaZrO3 ‐based nanoparticles growing from the host oxide under oxidizing atmosphere by liberating Ba/Zr cations from A/B‐sites readily forms proton transfer channels. The surface reconstructing heterostructures improve the structural stability, reduce the thermal expansion, and accelerate the oxygen reduction catalytic activity of such nanocomposite cathodes. This design route significantly boosts electrochemical performance with maximum peak power densities of 1453 and 992 mW cm −2 at 700 and 650 °C, respectively, 86% higher than the parent PrBaCo2 O5+δ cathode, accompanied by a much improved operational durability of 140 h at 600 °C. Abstract : A highly efficient strategy to construct the triple‐conductive heterostructure through surface protonation based on the robust double‐perovskite PrBaCo1.92 Zr0.08 O5+δ is proposed. BaZrO3 ‐based nanoparticles readily exsolve from the host oxide to form proton transfer channels, simultaneously improving the catalytic activity and structural stability. Button cells with PBCZ08 cathode show an excellent electrochemical performance of 1453 mW cm −2 at 700 °C.